A review of safety strategies of a Li-ion battery - Chombo, Pius Victor; Laoonual, Yossapong (Journal of power sources, 2020)
Since the burst of sales of electric vehicles in the world market, there have been frequently reported fire accidents throughout the globe. These accidents have led into the demise of occupants and vehicles which demoralize end-users. Herein, an extensive review of the thermal hazards of Li-ion battery and effective safety strategies toward eradicating the danger of thermal runaway is elucidated. First, the mechanism of thermal runaway (TR) and its associated chain reactions such as the breakdown of SEI layer, a reaction between anode/electrolyte, breakdown of electrolyte, a reaction between electrodes, etc. which in turn, generates enormous heat energy and variety species of flammable gases, is explained. In pack level, the main concern is the propagation of TR to the adjacent batteries inside the module and between modules. The propagation events transmit thermic consequences to adjacent batteries and, finally, catastrophically damage the battery pack. Thus, to reduce the thermal hazard of Lithium-ion battery, adequate measures have been reviewed, such as usage of thermally protective separators, safety devices, flame retardants, passive cooling devices, and fire suppressants. To conclude, the main goal here is to provide a better understanding of the TR mechanism and safety strategies toward enhancing the safety of Lithium-ion battery. [Display omitted] •Overcharge and overheat are the ultimate initiator of the thermal runaway.•Battery additives and material modification enhance safety at a cost of performance.•Improved heat transfer and cutting-off thermal cascading failure secure pack safety.•The ability to stop fire and cool the battery define the best suppressing agent.•The promising materials and technology govern the development of futuristic battery.